Virtual Reality-Based Sensory Stimulation for Pediatric Disorders of Consciousness: A Pilot Study - Liang, Piao; Xu, Hong; Li, Sinan; Ren, Lei; Zhao, Xiaoke (Frontiers in Pediatrics, 2022)
Abstract Objective: The purpose of this study was to determine whether virtual reality-based sensory stimulation has the ability to improve the level of consciousness in pediatric disorders of consciousness compared with general rehabilitation. Methods: Thirty subjects were divided into a virtual reality (VR) group (n=15) and a control group (n=15). Subjects in the VR group received both general rehabilitation and exposure to VR videos; the control group received only general rehabilitation. The Glasgow Coma Scale (GCS), Coma Recovery Scale-Revised (CRS-R), and amplitude-integrated electroencephalogram (EEG) (aEEG) were used to measure the clinical behavioral response and neuroelectrophysiology before and after the treatment. The Glasgow Outcome Scale Extended Pediatric Revised (GOS-E Peds) was used to measure the social and personal functional ability after 3 months. Results: After 2 weeks of treatment, the CRS-R and GCS improved in both groups. However, the VR group had better results than the control group in the CRS-R (p=0.003) and GCS (p=0.045). There were no significant differences on aEEG in the two groups after treatment. According to the GOS-E Peds, the improvement of social and personal functional ability had no significant differences in the two groups. And there were no obvious adverse reactions in the two group during the treatment. Conclusions: A VR program help improve the level of consciousness in pediatric disorders of consciousness. To further explore the efficacy of VR, a large-sample randomized controlled trial is warranted.